2022
DOI: 10.3390/w14060970
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gases Trade-Off from Ponds: An Overview of Emission Process and Their Driving Factors

Abstract: Inland water bodies (particularly ponds) emit a significant amount of greenhouse gases (GHGs), particularly methane (CH4), carbon dioxide (CO2), and a comparatively low amount of nitrous oxide (N2O) to the atmosphere. In recent decades, ponds (<10,000 m2) probably account for about 1/3rd of the global lake perimeter and are considered a hotspot of GHG emissions. High nutrients and waterlogged conditions provide an ideal environment for CH4 production and emission. The rate of emissions differs according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…A recent global meta-analysis found that natural wetlands were "net sinks of atmospheric CO 2 and net sources of CH 4 and N 2 O, exhibiting the capacity to mitigate greenhouse effects due to negative comprehensive global warming potentials (GWPs; -.9 to -8.7 t CO 2 -eq ha −1 year −1 )" (Tan et al, 2020). This analysis and other studies further highlight that the spatio-temporal variability in GHG emission is primarily sensitive to changes in water temperature, surface water content, chlorophyll-a, soil nitrogen content, bulk density, and soil pH (Kumar et al, 2022;Liu et al;Malyan et al, 2022;Zhou et al, 2022).…”
mentioning
confidence: 66%
“…A recent global meta-analysis found that natural wetlands were "net sinks of atmospheric CO 2 and net sources of CH 4 and N 2 O, exhibiting the capacity to mitigate greenhouse effects due to negative comprehensive global warming potentials (GWPs; -.9 to -8.7 t CO 2 -eq ha −1 year −1 )" (Tan et al, 2020). This analysis and other studies further highlight that the spatio-temporal variability in GHG emission is primarily sensitive to changes in water temperature, surface water content, chlorophyll-a, soil nitrogen content, bulk density, and soil pH (Kumar et al, 2022;Liu et al;Malyan et al, 2022;Zhou et al, 2022).…”
mentioning
confidence: 66%
“…The pH range of water in inland fresh waterbodies is 6-8 globally. Particularly, water bodies in Ontario, Canada exhibited pH range 5.77-7.74 (Malyan et al, 2022; Figure 7 Pretreatment optimization for cotton fibre hydrolysis: (a) Evaluation of different pretreatment conditions for cotton fibre hydrolysis using 3% commercial cellulase blend (Ctec2) and 25 mg cotton (weight of cellulose). Hot water pretreatment was done at 90 °C for 1 h with constant stirring on hot plate.…”
Section: Discussionmentioning
confidence: 99%
“…The pH range of water in inland fresh waterbodies is 6–8 globally. Particularly, water bodies in Ontario, Canada exhibited pH range 5.77–7.74 (Malyan et al ., 2022 ; Perron and Pick, 2020 ). The pH of the denim industry effluent greatly varies from 4.5 to 10 depending upon the fabric and dye used (Hooshmand et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities in water samples were largely affected by the TN, TP, NO 3 (-)-N, and NO 2 (-)-N concentrations, and sediment was affected by Sed-OM and Sed-TN. Tetracycline, oxytetracycline, chlortetracycline, and sulfadiazine are the four dominant antibiotics in the wetland, and they had a major influence on microbial communities in both water and sediment samples (Wang et al, 2017;Han et al, 2019;Goyal et al, 2022;Malyan et al, 2022). Tetracyclines may have contributed more than sulphonamides in the abundance of sul1, sul2, and tetC gens in Honghu Lake (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%